Problems of Managing and Licensing The Apartment - Stevenson, Thio Jerry; Soerodjo, Irawan; Budi, Henry Soelistyo (SASI, 2023)
Introduction: The fulfillment of the right to housing is a national problem that must be resolved. Jakarta is the capital city of Indonesia which faces problems in fulfilling the right to housing. The apartment area has been built to respond to these problems.Purposes of the Research: The purpose of this study is to analyze the management and licensing of apartments in Jakarta City.Methods of the Research: This research is a normative juridical research. It uses several approaches, namely the statute approach, the conceptual approach, and the comparative approach. The type of data used consists of primary legal materials, namely the 1945 Constitution of the Republic of Indonesia, Law Number 1 of 2011 concerning Housing and Settlement Areas, Law Number 20 of 2011 concerning Apartments.Results of the Research: Based on the results of the study, it was found that there were many cases, for example the case in Decision concerning the Privatization of SPAM and the unilateral determination of BPPL between the Sentul City against PT Sentul City. Based on this case, there was a legal uncertainty regarding the management and licensing of the apartment area in Jakarta